DAMPAK PEMBERIAN PAKAN PELLET IKAN TERHADAP PERTUMBUHAN KIAPU (Pistia stratiotes, L) - Yusnida Bey; Sri Wulandari; Sukatmi ' (Program Studi Pendidikan Biologi, 2011)
This research have purposed to know about effect of fish palette to growth Kiapu that conducted in the strands of metal house in Biological education Laboratory FKIP UNRI and PKA Faperika UNRI at June-July 2007. This research is an experiment with complete Random Design (RAL) that includes 4 treatment on the dosis of palette about 0; 4,5; 6 and 7,5 gr/10 L each with 6 time retesting. The parameter have observed included chemical physics of water factor is ammonia, free of CO2, disolved oxygen, pH and temperatur, while biology factor have observed is the growth of kiapu enveloped long of roots, sum up roots, wide of leafs, sum of leafs and sum of seeds. The growth of Kiapu data have analyzed with the ANOVA with the DMRT continued test on 5% of significance. The results of research indicate that gift palette of fish is effecting to water quality (ammonia, free of CO2 and disolved oxygen concentration) affecting also to biology factor of Kiapu is long of roots, sum up roots, sum up leafs and sum up seeds except wide leafs. On the A2 (6 gr/10 L) is effective for increasing sum up roots, sum up leafs and sum up seeds.